(untitled) (Global Journal of Medical Research, 2011)
Nigeria currently accounts for about 10 percent of the global HIV burden, therefore tackling this devastating pandemic is very imperative. This study was conducted to assess the level of patients#x2019; adherence to antiretroviral therapy and identify the factors responsible for non adherence in a major HIV/AIDS specialist hospital, Sobi, Ilorin, Nigeria. Adherence among 213 HIV infected patients on highly active antiretroviral therapy was assessed using self-reporting and pill counting methods for 20 months of therapy. Structured questionnaire, personal interview and patients#x2019; hospital records were used to evaluate access to medicines and patients#x2019; factors responsible for treatment adherence. Though, the level of patients#x2019; adherence to antiretroviral drugs was low (73.3%) compared with the standard (95%), there was significant improvement compared with the earlier reported in the sub-Saharan African countries including Nigeria. Low level of education of patients, adverse antiretroviral drug effects and stigmatization were the main factors given for non adherence. Thus, Nigeria government and non-governmental organizations should intensify efforts by improving the standard of education of the citizenry, increasing the level of awareness and encouragement on HIV/AIDS status as well as continuing funding to the rural communities to stem the tide of the menace.